Fine-Tuning Temulawak (Curcuma xanthorrhiza Roxb) Extraction: Solvent Selection, Methodological Approaches, and Optimization on Operating Condition - Korleone, Jorgi; Mufidah, Elya; Argo, Bambang Dwi; Sidauruk, Jocelyn Latreia Ronauli; Takase, Hayato; Izza, Ni'matul (Journal of Tropical Agricultural Engineering and Biosystems - Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2024)
Temulawak (Curcuma xanthorrhiza Roxb) is rich in bioactive compounds: phenols and flavonoids, working as antioxidants to counteract free radicals in the human body, in which appropriate extraction methods and solvents are required to obtain the total phenol and flavonoid content from this plant. Correlating to this, Response Surface Methodology (RSM) provides an analytical framework based on mathematical models to determine the conditions of optimal temulawak extraction. The study, therefore, aims to identify the best extraction method and solvent for extracting phenolic and flavonoid compounds from temulawak, to subsequently utilize the method in determining the optimal temulawak extraction conditions based on RSM using DesignExpert12 software. The results signify the best combination of extraction method and solvent is demonstrated by microwave-assisted extraction (MAE) using 70% ethanol. Additionally, the software showed that a solvent-to-material ratio of 66mL/g, with extraction power of 450 watts, and extraction time of 1 minute are required to perform the extraction under optimal conditions, resulting a total phenolic content (TPC) of 12.93±1.43 mg GAE/g dw and a total flavonoid content (TFC) of 21.79±0.98 mg QE/g dw through the verification process.